Adaptive immune response to whole cell pertussis vaccine reflects vaccine quality: A possible complementation to the Pertussis Serological Potency test. Issue 37 (17th August 2016) - Hoonakker, M.E.; Verhagen, L.M.; van der Maas, L.; Metz, B.; Uittenbogaard, J.P.; van de Waterbeemd, B.; van Els, C.A.C.M.; van Eden, W.; Hendriksen, C.F.M.; Sloots, A.; Han, W.G.H.
Abstract: Whole cell Bordetella pertussis (wP) vaccines are still used in many countries to protect against the respiratory disease pertussis. The potency of whole-cell pertussis vaccine lots is determined by an intracerebral challenge test (the Kendrick test). This test is criticized due to lack of immunological relevance of the read-out after an intracerebral challenge with B. pertussis . The alternative in vivo test, which assesses specific antibody levels in serum after wP vaccination, is the Pertussis Serological Potency test (PSPT). Although the PSPT focuses on a parameter that contributes to protection, the protective immune mechanisms after wP vaccination includes more elements than specific antibody responses only. In this study, additional parameters were investigated, i.e. circulating pro-inflammatory cytokines, antibody specificity and T helper cell responses and it was evaluated whether they can be used as complementary readout parameters in the PSPT to assess wP lot quality. By deliberate manipulation of the vaccine preparation procedure, a panel of high, intermediate and low quality wP vaccines were made. The results revealed that these vaccines induced similar IL-6 and IP10 levels in serum 4 h after vaccination (innate responses) and similar antibody levels directed against the entire bacterium. In contrast, the induced antibody specificity to distinct wP antigens differed after vaccination with high, intermediate and low quality wP vaccines. In addition, the magnitude of wP-induced Th cell responses (Th17, Th1 and Th2) was reduced after vaccination with a wP vaccine of low quality. T cell responses and antibody specificity are therefore correlates of qualitative differences in the investigated vaccines, while the current parameter of the PSPT alone was not sensitive enough to distinguish between vaccines of different qualities. This study demonstrates that assessment of the magnitude of Th cell responses and the antigen specificity of antibodies induced by wP vaccination could form valuable complementary parameters to the PSPT.